Closing Age and Race Gaps in Elections Through Inclusive and Contextual Communications - Julia Fisher Cummings (Journal of Social Equity and Public Administration)
This study seeks to learn how viewing political communications with varying attention to diversity, equity, and inclusion affects the intention to vote in the next election. The investigation examines voting disparities by considering power imbalances in political communications. It features a randomized experiment with 416 individuals (ages 18 to 30) in Denver, Colorado. Survey participants saw one of two virtual political postcards describing a minimum wage policy issue, each with varying attention to DEI. The study identifies voting deserts, defined as precincts with the highest percentage of nonvoters in the previous presidential election. Findings reveal that Asian, Black, Latiné, multiracial individuals, and women are more likely to intend to vote after viewing imagery with more attention to DEI. Implications are discussed for how public administrators and community-based organizations can strive to close age and race gaps in elections by driving voter turnout and building political power in marginalized communities.